Elevated levels of VCA0117 (VasH) in response to external signals activate the type VI secretion system of Vibrio cholerae O1 El Tor A1552. (10th July 2020) - Seibt, Henrik; Aung, Kyaw Min; Ishikawa, Takahiko; Sjöström, Annika; Gullberg, Martin; Atkinson, Gemma Catherine; Wai, Sun Nyunt; Shingler, Victoria
Summary: The type VI nanomachine is critical for Vibrio cholerae to establish infections and to thrive in niches co‐occupied by competing bacteria. The genes for the type VI structural proteins are encoded in one large and two small auxiliary gene clusters. VCA0117 (VasH) – a σ 54 ‐transcriptional activator – is strictly required for functionality of the type VI secretion system since it controls production of the structural protein Hcp. While some strains constitutively produce a functional system, others do not and require specific growth conditions of low temperature and high osmolarity for expression of the type VI machinery. Here, we trace integration of these regulatory signals to the promoter activity of the large gene cluster in which many components of the machinery and VCA0117 itself are encoded. Using in vivo and in vitro assays and variants of VCA0117, we show that activation of the σ 54 ‐promoters of the auxiliary gene clusters by elevated VCA0117 levels are all that is required to overcome the need for specialized growth conditions. We propose a model in which signal integration via the large operon promoter directs otherwise restrictive levels of VCA0117 that ultimately dictates a sufficient supply of Hcp for completion of a functional type VI secretion system.